RELIABILITAS DAN AVAILABILITAS SISTEM TIGA KOMPONEN TERSUSUN PARALEL BERSERI - Sudarno Sudarno; Rukun Santoso; Avida Anugraheni (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2018)
Reliability is the ability of a product or an item to maintain the required function of a specified period of time under given operating conditions. Availability is a measure of system performance and measures the combined effect of reliability, maintenance and logistic support on the operational effectivesness of the system. The system was formedby some components. This system could be broken, then it could not be operated. In order to system could operate again, it should be repaired. This system consist of three components, such that component-1 is a processor core, component-2 is interface input/output, and component-3 is memory. The system was arranged by parallel-seri.This paper use generation data. Data are failure time and repair time of components of system, respectively. Therefore, research variables are failure time and repair time of all component of system. The aim of this research is finding the mean time to failure and the mean time to repair components, reliability of system, and availability of system.The research result of reliability of system is 0.9998 while availability of system is 0.9987. These results could be concluded that system have best quality and high performing. Generally, if reliability value was higher then quality of system more perfect and if availability value was higher then perform of system was better. Keywords : Reliability, availability, mean time to failure, mean time to repair.